Retinoic acid supplementation attenuates ventricular remodeling after myocardial infarction in rats - Paiva, Sergio Alberto Rupp de [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Campana, Álvaro O. [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (My University, 2005)
The objective of this study was to evaluate the role of retinoic acid in experimental postinfarction myocardial remodeling. Wistar rats were subjected to myocardial infarction (MI) and treated with retinoic acid (RA), 0.3 mg/(kg · d) (MI-RA, n = 29), or fed a control diet (MI, n = 34). After 6 mo, the surviving rats (MI-RA = 18 and MI = 22) underwent echocardiograms, and isolated hearts were tested for function in vitro. The cross-sectional area of the myocyte (CSA) and interstitial collagen fraction (IC) were measured in a cross section of the heart stained by hematoxylin-eosin and picrosirius red, respectively. The CSA was smaller in the MI-RA group [229 (220, 234) μm 2] [medians (lower quartile, upper quartile)] than in the MI group [238 (232, 241) μm 2] (P = 0.01) and IC was smaller in the MI-RA group [2.4 (1.7, 3.1)%] than in the MI group [3.5 (2.6, 3.9)%] (P = 0.05). The infarct size did not differ between the groups [MI = 44.6 (40.8, 48.4)%, MI-RA = 45 (38.6, 47.2)%]. Maximum rate of rise of left ventricular pressure (+dp/dt) was greater in the MI-RA group (2645 ± 886 mm Hg/s) than in the MI group (2081 ± 617 mm Hg/s) (P = 0.05). The other variables tested did not differ between groups. Retinoic acid supplementation of rats for 6 mo attenuates the ventricular remodeling process after MI. © 2005 American Society for Nutrition.
Keywords: Myocardial fibrosis; Remodeling; Retinoids; Ventricular function; collagen; dye; eosin; hematoxylin; picrosirius red; retinoic acid; unclassified drug; animal experiment; animal model; animal tissue; conference paper; controlled study; echocardiography; heart infarction; heart left ventricle pressure; heart muscle cell; heart ventricle remodeling; in vitro study; isolated heart; lung function; male; nonhuman; rat; staining; survival; treatment outcome; Animals; Antineoplastic Agents; Male; Myocardial Infarction; Rats; Rats, Wistar; Tretinoin; Ventricular Dysfunction, Left; Ventricular Function, Left; Ventricular Remodeling; Animalia; Rattus norvegicus